EMOTIONAL INTELLIGENCE AND MOTIVATION AS SCHOOL MANAGEMENT STRATEGIES IN THE EDUCATIONAL PROCESS (International Seven Journal of Multidisciplinary, 2025)
This article addresses the importance of emotional intelligence and motivation as fundamental strategies for school management in the educational process. Recognizing the school as a complex space, comprised of diverse individuals across their cognitive, emotional, and social dimensions, the research emphasizes the role of the management team in building school environments that promote well-being, learning, and ethical coexistence. Through a bibliographical approach, recent studies were analyzed that demonstrate the relevance of socio-emotional competencies for educational leadership, highlighting the need for ongoing training and the adoption of practices that value active listening, dialogue, and emotional recognition. Motivation is presented as a determining factor for student and staff engagement, being enhanced by the creation of institutional conditions that foster autonomy, belonging, and appreciation. Emotional intelligence, in turn, contributes to conflict mediation, bonding, and the promotion of a healthy organizational climate. The integration of these dimensions strengthens the transformative role of school management, which must act strategically and humanely, promoting the comprehensive development of those involved in the educational process. The study highlights the need for public policies that support leadership development in emotional and motivational aspects, highlighting the contribution of these competencies to achieving a quality, inclusive, and meaningful education. Thus, the research concludes that school management, by incorporating emotional intelligence and motivation into its practices, enhances the creation of welcoming and productive educational environments that foster the full development of students and the strengthening of the school community.